7 - Towards Post-Coronial Futures: COVID-19, Rapid Digital Transformation and University Responsiveness - Wangenge-Ouma, Gerald (CODESRIA Bulletin, 2022)
Dramatic COVID-19-inspired changes – upended economies, exacerbated job losses, inequalities, major so- cial deprivation and accelerated digital transformation – occurring in the structure and scope of higher edu- cation institutions have put a premium on responsiveness to change. As open systems, universities are affected by contingencies in their environment, including complex demands, which they have to respond to in order to enhance their adaptability and societal relevance. This paper examines the dramatic changes occurring in the external environment of universities in the context of COVID-19, especially accelerated digital transforma- tion, and maps various response trajectories and reconfigurations by universities as they reposition for the yet unknown post-pandemic era.